Immobilization of copper complexes with (1, 10-phenanthrolinyl)phosphonates on titania supports for sustainable catalysis. Issue 24 (30th May 2017) - Mitrofanov, Alexander; Brandès, Stéphane; Herbst, Frédéric; Rigolet, Séverinne; Bessmertnykh-Lemeune, Alla; Beletskaya, Irina
Abstract : Immobilization of copper complexes with 1, 10-phenanthroline functionalized by phosphonate anchoring groups was investigated to prepare porous and reusable catalysts for Sonogashira-type and Huisgen cycloaddition reactions. Abstract : Different strategies for the immobilization of copper complexes with 1, 10-phenanthroline (phen ) using the phosphonate anchoring group were investigated to prepare robust and porous heterogeneous catalysts. Homoleptic and heteroleptic copper(i ) complexes withphen bearing the bis(trimethylsiloxy)phosphoryl anchoring group (Pphen-Si ) at different positions of thephen backbone were prepared and covalently incorporated into titania (TiO2 ) xerogels by using the sol–gel process or grafted onto the surface of mesoporous TiO2 ( S BET = 650 m 2 g −1 ). Copper(i ) bis(Pphen-Si ) complexes were the only complexes that were successfully anchored onto the TiO2 surface because the heterogenization was often accompanied by the undesirable dissociation of copper complexes. Hybrid materials based on copper(i ) chelates with onephen ligand were obtained following a two-step procedure involving the immobilization ofPphen-Si chelators and their successive complexation with copper(i ) ions. Porous material, Cu/6b/SM/A, displaying a BET surface area of 243 m 2 g −1 and bearing 0.57 mmol g −1 of the complex was synthesized according to this approach. Excellent catalytic performance of the reusableCu/6b/SM/A material in the Sonogashira-type coupling and the Huisgen 1, 3-dipolar cycloaddition was also demonstrated. This solid represents the first example of mesoporous TiO2 -supported transition metal catalysts.